HUBUNGAN PERILAKU MEROKOK PADA REMAJA DENGAN PRESTASI BELAJAR DI SMK PGRI PRINGSEWU - Kusuma Wardani, Psiari; Puspita, Linda (Jurnal Kelitbangan Bappeda Pringsewu, 2017)
Smoking is a problem that has not been resolved to date. Smoking has hit the various circles, both children to parents, men and women, especially in high school students. Many factors can cause the students to smoke. Allegedly several factors that influence smoking behavior include the influence of parents, the influence of friends, personality factors and because of advertising. This study aims to determine the relationship between smoking behavior in adolescents class XI at SMK PGRI Pringsewu 2014. To know the proportion of smoking behavior in adolescents at SMK PGRI Pringsewu 2014. To determine the proportion of student achievement in SMK PGRI Pringsewu 2014. Research This is an analytical research with cross sectional approach. Research population of all students of class XI SMK PGRI Pringsewu which amounted to 90 people. Sampling technique used saturated sample by using the entire population. Data analysis used univariate and bivariate analysis using chi square test. The result of univariate research got smoking teenager that is 68 responden and less learning achievement as much 49 responder. Chi-square statistic test results there are correlation between smoking behavior in adolescents with learning achievement (11,47> 3,481). The conclusion of the research indicates that there is a relationship between smoking behavior in adolescents with learning achievement. It is hoped that the counseling about the dangers of smoking in schools will be done by cooperating between health workers and schools.